Evaluation of cyclooxygenase-2 fluctuation via a near-infrared fluorescent probe in idiopathic pulmonary fibrosis cell and mice models. Issue 31 (28th July 2021) - Wang, Yude; Wei, Yinghui; He, Na; Zhang, Liangwei; You, Jinmao; Chen, Lingxin; Lv, Changjun
Abstract : The near-infrared fluorescent probe, Cy-COX, evaluated Cyclooxygenase-2 in idiopathic pulmonary fibrosis cells and mice models. Abstract : Idiopathic pulmonary fibrosis (IPF) is a devastating and fatal interstitial lung disease due to various challenges in diagnosis and treatment. Due to its complicated pathogenesis and difficulty in early diagnosis, there is no effective cure. Cyclooxygenase-2 (COX-2) is inextricably associated with pulmonary fibrosis. The abnormal level of COX-2 leads to extremely exacerbated pulmonary fibrosis. Therefore, we reported a near-infrared fluorescent probe Cy-COX to detect the fluctuation of COX-2 levels during pulmonary fibrosis and explain its important protective effect. The probe Cy-COX showed a significant enhancement of fluorescence signal to COX-2 with excellent selectivity and sensitivity. In order to clarify the relationship between COX-2 and pulmonary fibrosis, we used the probe Cy-COX to detect COX-2 fluctuation in organisms with pulmonary fibrosis. The results showed that the COX-2 level increased in the early stage and decreased in the late stage with the aggravation of pulmonary fibrosis. Furthermore, up-regulation of COX-2 levels can effectively alleviate the severity of pulmonary fibrosis. Therefore, Cy-COX is a fast and convenient imaging tool with great potential to predict the early stage of pulmonary fibrosis and evaluate the therapeutic effects.